The insurance technology in the Philippines its future through scenario building and relevance tree analysis - Florencio, Juan Carlo R. (University of the Philippines Diliman, 2023)
This capstone project explores Insurance Technology's (InsurTech) potential in the Philippines and presents a comprehensive strategy to drive its growth and adoption. The project begins by identifying focal issues in the insurance sector, including client engagement, fraud prevention, risk assessment, claims processing, and regulatory compliance. Through an extensive analysis of emerging trends, scenario building, and relevance tree analysis, three distinct scenarios are developed, highlighting the transformative impact of technology on the insurance landscape.